The Influence of Teacher Working Group Activities (KKG) on Elementary School Teachers' Professional Competence - Fauziyah Hanif; Marzuki Noor; Sujino Sujino (Institut Agama Islam Sunan Giri Ponorogo, 2026)
Teacher Working Groups (KKG) serve as vital forums for professional collaboration, yet their specific impact requires empirical validation. This study aimed to analyze the influence of KKG activities on the professional competence of elementary school teachers in East Metro District, Lampung Province, Indonesia. Employing a quantitative survey method, data were collected from 72 teachers selected via the Slovin formula and purposive sampling from a population of 251, using a validated Likert-scale questionnaire. Data were analyzed using simple linear regression, t-tests, and coefficient of determination. Results revealed that KKG activities significantly and positively affect professional competence (t = 5.692, p < 0.001), with the regression equation Y = 29.940 + 0.825X indicating each unit increase in KKG activity raises competence by 0.825 points. KKG activities contributed 31.6% (R² = 0.316) to professional competence, while other factors accounted for 68.4%. In conclusion, KKG plays a crucial role in enhancing teachers' professional competence, highlighting the importance of fostering collaborative forums to support continuous educator development.